Past, Present and Future Trends in Cotton Breeding 2018
DOI: 10.5772/intechopen.74648
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Extremes in Cotton Production and Mitigation Strategies

Abstract: Cotton is an important cash crop, providing raw material for different industries and plays crucial role in the economy of several countries. It requires optimum temperature for economic production and causes reduced yield otherwise. Extreme temperature, more importantly, high temperature causes serious yield reduction in cotton by affecting its physiology, biochemistry and quality leading to poor agronomic produce. Freezing temperature also affect the germination percentage and seedling establishment. Several… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 121 publications
2
32
0
Order By: Relevance
“…Cotton production is facing several biotic and abiotic challenges including CLCV (Cotton leaf curl virus), wilting disease, sucking and chewing insect pests, drought and elevated temperature. In recent years, high temperature has been reported as a serious threat to crop productivity (Zafar et al 2018). So, when cotton is exposed to high temperature for longer duration lead to wilting of leaf (Ahuja et al 2010;Zahid et al 2016), shedding of fruiting bodies, i.e., squares, buds, flowers and bolls (Cao et al 2008;Iqbal et al 2017), and decreased rate of photosynthesis is reported by Marchand et al (2005).…”
Section: Discussionmentioning
confidence: 99%
“…Cotton production is facing several biotic and abiotic challenges including CLCV (Cotton leaf curl virus), wilting disease, sucking and chewing insect pests, drought and elevated temperature. In recent years, high temperature has been reported as a serious threat to crop productivity (Zafar et al 2018). So, when cotton is exposed to high temperature for longer duration lead to wilting of leaf (Ahuja et al 2010;Zahid et al 2016), shedding of fruiting bodies, i.e., squares, buds, flowers and bolls (Cao et al 2008;Iqbal et al 2017), and decreased rate of photosynthesis is reported by Marchand et al (2005).…”
Section: Discussionmentioning
confidence: 99%
“…The increase of Temperature and irregular and heavy rainfall have already affected crop production in many parts of Bangladesh [19]. An increase of 4°C in temperature would have a severe impact on food production in Bangladesh as resulting in a 28 per cent reduction for rice and a 68 percent reduction for wheat [20].…”
Section: Climate Changementioning
confidence: 99%
“…Abiotic stresses such as drought, salinity and suboptimal temperature are serious threats for agriculture and global food security [1,2]. These stresses negatively affect plant growth and development and ultimately result in poor crop production [3][4][5]. Rice is a major grain crop and feeds about half of the world population [6,7].…”
Section: Introductionmentioning
confidence: 99%